Oxygen Dependence of Formation, Electronic State Transition, and Spin Polarization for Anatase TiO2: A Comprehensive Study - L. L. Shan; R. M. Fan; Y. Sun; F. P. Zhang; G. L. Zhang; G. Q. Qin (Advances in Condensed Matter Physics)
The stability, geometry, microstructure, and specie combination together with the electronic states of the anatase TiO2 with oxygen defect content of 0%, 3.125%, 6.25%, and 12.5% have been intensively studied within the framework of the density functional theory method. The results show that the TiO2 with an oxygen defect is not as stable as intrinsic TiO2. The compound formation enthalpy Ef and the oxygen defect formation energy value tend to be larger for a higher defect content, and the oxygen defect gets harder to be formed. The bonds within the TiO6 polyhedron are different and not geometrically symmetrical. The bond strengths show distinct diversity, and the primitive cell of anatase TiO2 show spatial expansion when there are oxygen defects. All bands moved down to the low energy region, and two impurity energy band levels emerged for the anatase TiO2 with oxygen defect. The energy band gap is decreased from 3.085 eV to 1.165 eV, 1.0015 eV, and 0.43 eV. There are generally 7 peaks for the spin density of states function, corresponding to their 5 main bands. For the anatase TiO2 with an oxygen defect content of 12.5%, the spin density of states functions are not horizontal ordinate symmetrical near −1.12 eV and 0.31 eV. They are formed by oxygen defect energy levels, which is the result of the Ti d and O p state electron polarization. Transitions from weak paramagnetic to antiferromagnetic are found for the anatase TiO2 with oxygen defect.